Weather-resistant coating for photovoltaic module and preparation method of weather-resistant coating

By using a weather-resistant coating composed of modified resin and composite filler on the photovoltaic module, the problem of reduced power generation efficiency and shortened service life of the photovoltaic module in harsh environments is solved, and the weather resistance performance of the coating is improved and the life of the photovoltaic system is extended.

CN119592156AInactive Publication Date: 2025-03-11JIANGSU TIANYI ENERGY CO LTD

Patent Information

Application Number
CN202510123124.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When photovoltaic modules operate outdoors for a long time, they face harsh environments such as high temperature, high humidity, and strong ultraviolet rays, resulting in reduced power generation efficiency and shortened service life. Existing paints are difficult to meet application needs in extreme environments.

Method used

A weather-resistant coating for photovoltaic modules is adopted, which consists of a modified resin, a curing agent, a composite filler, an auxiliary agent, a solvent and a plasticizer. The modified resin enhances the UV resistance through specific synthesis methods, and the composite filler improves the water resistance, corrosion and antibacterial properties of the coating through modification of nano zinc oxide and cinnamic acid.

Benefits of technology

It significantly improves the weather resistance of the coating, extends the service life of the photovoltaic system, and broadens its application fields. The coating not only maintains excellent characteristics in harsh environments, but also has good UV resistance, corrosion resistance, water resistance and antibacterial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a weather-resistant coating for a photovoltaic module and a preparation method of the weather-resistant coating, and belongs to the technical field of high polymer materials. The modified epoxy resin adhesive comprises the following components in parts by weight: 90-120 parts of modified resin, 5-25 parts of a curing agent, 10-30 parts of a composite filler, 5-10 parts of an auxiliary agent, 5-40 parts of a solvent and 0.5-3 parts of a plasticizer, a benzotriazole structure and a benzophenone group in the modified resin cooperate to enhance ultraviolet resistance and prolong service life, and introduced 1H, 1H-perfluoropropyl methacrylate is short in C-F bond and high in bond energy, so that moisture resistance and corrosion resistance are improved; long-carbon-chain silane in the composite filler modifies nano-zinc oxide, so that super-hydrophobicity is realized, cracks on a resin curing surface are filled, and corrosion resistance and wear resistance are enhanced; in addition, cinnamic acid endows the coating with excellent antibacterial ability, and the weather-resistant coating for the photovoltaic module prepared by the invention not only has good ultraviolet resistance, high temperature resistance and corrosion resistance, but also has excellent water-resistant and antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a weather-resistant coating for a photovoltaic module and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology and the continuous development needs of the industry, building a green, low-carbon, efficient and clean renewable energy supply system has become a future development trend. Photovoltaic building integration not only improves the beauty of the building by integrating photovoltaic components into the building design, but also achieves self-sufficiency in electricity, effectively avoiding environmental pollution.

[0003] However, photovoltaic modules operate in outdoor environments for a long time and face various harsh climatic conditions such as high temperature, high humidity, and strong ultraviolet rays, which reduce their power generation efficiency and shorten their service life. Although coatings, as an important protective layer of photovoltaic modules, have the characteristics of water resistance, moisture and heat resistance, and weather resistance, they are still insufficient in extreme environments and cannot meet the growing application needs. Therefore, in-depth modification research on the weather resistance of photovoltaic module coatings to enhance their ability to resist external damage, extend the overall life of photovoltaic systems, and expand the application areas of weather-resistant coatings for photovoltaic modules has become an important direction for current industry technological innovation and development.‌ Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a weather-resistant coating for a photovoltaic module and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A weather-resistant coating for photovoltaic modules, comprising the following raw materials in parts by weight: 90-120 parts of modified resin, 5-25 parts of curing agent, 10-30 parts of composite filler, 5-10 parts of auxiliary agent, 5-40 parts of solvent, and 0.5-3 parts of plasticizer; The curing agent is hexamethylene diisocyanate; The auxiliary agent is dibutyltin dilaurate; The solvent is butyl acetate; The plasticizer is polyethylene glycol.

[0006] The modified resin is prepared by the following method: Step A1: 3-amino-4-hydroxybenzoic acid, sodium nitrite, copper sulfate pentahydrate and concentrated hydrochloric acid are mixed, stirred in an ice-salt bath at 0-5°C, the pH is adjusted to 7-8, 11-aminoundecyltrimethoxysilane, ethanol-water mixed solution and hydroxypropyl methacrylate are added, and the mixture is mixed at 35°C for 10 minutes, and then the mixture is heated to 60°C, filtered and washed to obtain intermediate 1; Further, the dosage ratio of 3-amino-4-hydroxybenzoic acid, sodium nitrite, copper sulfate pentahydrate, concentrated hydrochloric acid, 11-aminoundecyltrimethoxysilane, ethanol-water mixed solution, and hydroxypropyl methacrylate is 1-1.5 g: 0.69 g: 1.04-1.19 g: 3 mL: 5-7 g: 5-7 g: 2-4 g, and the volume ratio of ethanol to water in the ethanol-water mixed solution is 4:1; Step A2: m-phenylenediamine and intermediate 1 are mixed, heated to 25°C, reacted for 2h, and under nitrogen protection, 4'-chloro-2-hydroxy-4-methoxybenzophenone and dioxane are added, mixed and stirred, heated to 65°C, reacted for 6h, filtered, washed, and dried at 45°C to obtain intermediate 2; Further, the usage ratio of m-phenylenediamine, intermediate 1, 4'-chloro-2-hydroxy-4-methoxybenzophenone, and dioxane is 6.0 g: 6-8 g: 1.0-2.2 g: 10-20 mL; Step A3: Methyl methacrylate, butyl acrylate, intermediate 2, 1H,1H-perfluoropropyl methacrylate and methacrylic acid were mixed, stirred for 10 min, and then azobisisobutyronitrile, dodecanethiol and ethanol were added and stirred to mix evenly, heated to 70-80° C., reacted for 3 h, and cooled to room temperature to obtain a modified resin; Furthermore, the usage ratio of methyl methacrylate, butyl acrylate, intermediate 2, 1H,1H-perfluoropropyl methacrylate, methacrylic acid, azobisisobutyronitrile, dodecanethiol and ethanol is 5-7g:5-7g:2-4g:0.5-1.5g:0.3-0.7g:0.35-0.55g:0.5-1.5mL:20mL.

[0007] The composite filler is prepared by the following method: Step B1: Mix nano zinc oxide and toluene, place in a constant temperature water bath, stir at 80°C for 15 minutes, add dodecyltrimethoxysilane, react at 80°C for 9 hours, then add γ-aminopropyltriethoxysilane, react at 80°C for 8 hours, centrifuge, wash, ultrasonically disperse and clean, centrifuge, dry at 60°C, and grind to obtain super hydrophobic zinc oxide; Further, the dosage ratio of nano zinc oxide, toluene, dodecyltrimethoxysilane, and γ-aminopropyltriethoxysilane is 2.5-4 g: 80-100 mL: 1-2 mL: 0.1-0.25 mL; Step B2: Super-hydrophobic zinc oxide and anhydrous ethanol are mixed, ultrasonically dispersed for 30 minutes, and cinnamic acid is added under nitrogen protection, heated to 60° C., reacted for 3 hours, centrifuged, washed, and dried at 45° C. to obtain a composite filler; Furthermore, the usage ratio of superhydrophobic zinc oxide, anhydrous ethanol and cinnamic acid is 60-100 g: 120-200 mL: 5-7 g.

[0008] A method for preparing a weather-resistant coating for a photovoltaic module comprises the following steps: S1, placing the modified resin in a solvent and ultrasonically treating it for 10-20 minutes to obtain a dispersion; S2, adding the composite filler, plasticizer, curing agent and additive into the dispersion and stirring for 5-10 minutes to mix evenly to obtain a mixed coating; S3. Stir the mixed coating in a vacuum environment to remove bubbles and let it stand for 5-15 minutes, and then cure it at 70-80°C for 36-48 hours to obtain a weather-resistant coating for photovoltaic modules.

[0009] Beneficial effects of the present invention: The modified resin prepared by the present invention comprises the following steps: firstly, the carboxyl group of 3-amino-4-hydroxybenzoic acid reacts with the amino group of 11-aminoundecyltrimethoxysilane, and simultaneously, the hydrolyzed silanol group of 11-aminoundecyltrimethoxysilane reacts with the hydroxyl group of hydroxypropyl methacrylate to synthesize an intermediate 1; then, the intermediate 1 reacts with m-phenylenediamine to generate a benzotriazole structure, and the amino group thereof reacts with the chlorine atom of 4'-chloro-2-hydroxy-4-methoxybenzophenone to generate an intermediate 2; finally, azobisisobutyronitrile is used as an initiator, and methyl methacrylate, butyl acrylate, the intermediate 2, 1H,1H-perfluoropropyl methacrylate and methacrylic acid are copolymerized to synthesize the modified resin. In the modified resin, the benzotriazole structure of intermediate 2 and 4'-chloro-2-hydroxy-4-methoxybenzophenone work synergistically to enhance the UV resistance and extend the service life of the material; intermediate 2 containing benzotriazole can effectively absorb ultraviolet rays in different wavelength ranges and convert them into energy, reducing the damage of ultraviolet rays to the material. At the same time, the addition of 4'-chloro-2-hydroxy-4-methoxybenzophenone containing benzophenone further enhances the UV resistance and prevents UV-induced aging, while avoiding the migration, incompatibility and volatilization problems of traditional UV absorbers; in addition, the introduced 1H, 1H-perfluoropropyl methacrylate, with its short bond and high bond energy CF bond, gives the coating excellent stability, exhibits excellent moisture resistance and corrosion resistance, and greatly improves the weather resistance of the coating. ‌‌ The composite filler prepared by the present invention first utilizes the silanol of dodecyl trimethoxy silane to react with the hydroxyl group on the surface of nano zinc oxide, condenses to form a silicon oxygen bond, and then uses γ-aminopropyl triethoxy silane for modification to obtain a super hydrophobic zinc oxide modified by a double silane coupling agent; secondly, the amino group of γ-aminopropyl triethoxy silane and the carboxyl group of cinnamic acid are condensed to form an amide bond to obtain a composite filler. In the composite filler, long carbon chain dodecyl trimethoxy silane modifies the surface of nano zinc oxide, giving it super hydrophobic characteristics, and significantly improving the water resistance of the coating; nano zinc oxide can not only effectively fill the cracks and holes on the surface of the resin curing, extend the path of water penetration to the matrix, and enhance the anti-corrosion performance of the coating, but also form a three-dimensional network structure with the resin, improve the adhesion, hardness and wear resistance of the coating, and extend the service life of the coating in harsh environments; in addition, the introduced cinnamic acid can inhibit protein synthesis, destroy the cell membrane and cell wall in the bacteria, effectively inhibit the reproduction of bacteria and inactivate them, thereby giving the coating excellent antibacterial ability.

[0010] The weather-resistant coating for photovoltaic modules prepared by the present invention not only has good UV resistance and corrosion resistance, but also has excellent water resistance and antibacterial effects, thereby effectively extending the service life of the material. The weather-resistant coating for photovoltaic modules prepared has excellent weather resistance and can maintain excellent properties in harsh environments, which is of great significance for application scenarios in harsh environments. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Embodiment 1: A method for preparing a weather-resistant coating for a photovoltaic module, comprising the following steps: S1. Weigh the raw materials by weight: 90 parts of modified resin (prepared in this example), 5 parts of curing agent, 10 parts of composite filler (prepared in this example), 5 parts of auxiliary agent, 5 parts of solvent, and 0.5 parts of plasticizer. Place the modified resin in butyl acetate and perform ultrasonic treatment for 10 minutes to obtain a dispersion; S2, adding the composite filler, polyethylene glycol, hexamethylene diisocyanate and dibutyltin dilaurate into the dispersion, stirring for 5 minutes to mix evenly to obtain a mixed coating; S3, stirring the mixed coating in a vacuum environment to remove bubbles and standing for 5 minutes, and curing at 70°C for 36 hours to obtain a weather-resistant coating for photovoltaic modules; The modified resin is prepared by the following method: Step A1: 1 g of 3-amino-4-hydroxybenzoic acid, 0.69 g of sodium nitrite, 1.04 g of copper sulfate pentahydrate and 3 mL of concentrated hydrochloric acid were mixed, stirred in an ice-salt bath at 0°C, the pH was adjusted to 7-8, and then 5 g of 11-aminoundecyltrimethoxysilane, 5 g of an ethanol-water mixed solution and 2 g of hydroxypropyl methacrylate were added, and the mixture was mixed at 35°C for 10 min, and then the mixture was heated to 60°C, filtered and washed to obtain an intermediate 1. The volume ratio of ethanol to water in the ethanol-water mixed solution was 4:1; Step A2: 6.0 g of m-phenylenediamine and 6 g of intermediate 1 were mixed, heated to 25°C, reacted for 2 h, and under nitrogen protection, 1.0 g of 4'-chloro-2-hydroxy-4-methoxybenzophenone and 10 mL of dioxane were added, mixed and stirred, heated to 65°C, reacted for 6 h, filtered, washed, and dried at 45°C to obtain intermediate 2; Step A3: 5 g of methyl methacrylate, 5 g of butyl acrylate, 2 g of intermediate 2, 0.5 g of 1H,1H-perfluoropropyl methacrylate and 0.3 g of methacrylic acid were mixed, stirred for 10 min, and then 0.35 g of azobisisobutyronitrile, 0.5 mL of dodecanethiol and 20 mL of ethanol were added and stirred to mix evenly, the temperature was raised to 70° C., the reaction was carried out for 3 h, and the modified resin was obtained by cooling to room temperature; The composite filler is prepared by the following method: Step B1: 2.5 g of nano zinc oxide and 80 mL of toluene were mixed, and the mixture was placed in a constant temperature water bath and stirred at 80° C. for 15 min. 1 mL of dodecyltrimethoxysilane was added, and the mixture was reacted at 80° C. for 9 h. 0.1 mL of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 80° C. for 8 h. The mixture was centrifuged, washed, ultrasonically dispersed and cleaned, and centrifuged. The mixture was dried and ground at 60° C. to obtain superhydrophobic zinc oxide. Step B2: 60 g of superhydrophobic zinc oxide and 120 mL of anhydrous ethanol were mixed, ultrasonically dispersed for 30 min, and 5 g of cinnamic acid was added under nitrogen protection. The mixture was heated to 60° C., reacted for 3 h, centrifuged, washed, and dried at 45° C. to obtain a composite filler.

[0013] Embodiment 2: A method for preparing a weather-resistant coating for a photovoltaic module, comprising the following steps: S1. Weigh the raw materials by weight: 105 parts of modified resin (prepared in this embodiment), 15 parts of curing agent, 20 parts of composite filler (prepared in this embodiment), 7 parts of auxiliary agent, 22 parts of solvent, and 1.7 parts of plasticizer. Place the modified resin in butyl acetate and perform ultrasonic treatment for 15 minutes to obtain a dispersion; S2, adding the composite filler, polyethylene glycol, hexamethylene diisocyanate and dibutyltin dilaurate into the dispersion, stirring for 7 minutes to mix evenly to obtain a mixed coating; S3, stirring the mixed coating in a vacuum environment to remove bubbles and standing for 10 minutes, and curing at 75°C for 42 hours to obtain a weather-resistant coating for photovoltaic modules; The modified resin is prepared by the following method: Step A1: 1.25 g 3-amino-4-hydroxybenzoic acid, 0.69 g sodium nitrite, 1.11 g copper sulfate pentahydrate and 3 mL concentrated hydrochloric acid were mixed, stirred in an ice-salt bath at 2°C, the pH was adjusted to 7-8, 6 g 11-aminoundecyltrimethoxysilane, 6 g ethanol-water mixed solution and 3 g hydroxypropyl methacrylate were added, and the mixture was mixed at 35°C for 10 min, and then the mixture was heated to 60°C, filtered and washed to obtain intermediate 1. The volume ratio of ethanol to water in the ethanol-water mixed solution was 4:1; Step A2: 6.0 g of m-phenylenediamine and 7 g of intermediate 1 were mixed, heated to 25°C, reacted for 2 h, and under nitrogen protection, 1.6 g of 4'-chloro-2-hydroxy-4-methoxybenzophenone and 15 mL of dioxane were added, mixed and stirred, heated to 65°C, reacted for 6 h, filtered, washed, and dried at 45°C to obtain intermediate 2; Step A3: 6 g of methyl methacrylate, 6 g of butyl acrylate, 3 g of intermediate 2, 1 g of 1H,1H-perfluoropropyl methacrylate and 0.5 g of methacrylic acid were mixed and stirred for 10 min, and then 0.45 g of azobisisobutyronitrile, 1 mL of dodecanethiol and 20 mL of ethanol were added and stirred to mix evenly, the temperature was raised to 75° C., the reaction was carried out for 3 h, and the modified resin was obtained by cooling to room temperature; The composite filler is prepared by the following method: Step B1: 3.2 g of nano zinc oxide and 90 mL of toluene were mixed, and the mixture was placed in a constant temperature water bath, stirred at 80°C for 15 min, 1.5 mL of dodecyltrimethoxysilane was added, and the mixture was reacted at 80°C for 9 h, and then 0.17 mL of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 80°C for 8 h, and then the mixture was centrifuged, washed, ultrasonically dispersed and cleaned, and centrifuged, and then dried and ground at 60°C to obtain superhydrophobic zinc oxide; Step B2: 80 g of superhydrophobic zinc oxide and 160 mL of anhydrous ethanol were mixed, ultrasonically dispersed for 30 min, and 6 g of cinnamic acid was added under nitrogen protection. The mixture was heated to 60° C., reacted for 3 h, centrifuged, washed, and dried at 45° C. to obtain a composite filler.

[0014] Embodiment 3: A method for preparing a weather-resistant coating for a photovoltaic module, comprising the following steps: S1. Weigh the raw materials by weight: 120 parts of modified resin (prepared in this embodiment), 25 parts of curing agent, 30 parts of composite filler (prepared in this embodiment), 10 parts of auxiliary agent, 40 parts of solvent, and 3 parts of plasticizer; place the modified resin in butyl acetate and perform ultrasonic treatment for 20 minutes to obtain a dispersion; S2, adding the composite filler, polyethylene glycol, hexamethylene diisocyanate and dibutyltin dilaurate into the dispersion, stirring for 10 minutes to mix evenly to obtain a mixed coating; S3, stirring the mixed coating in a vacuum environment to remove bubbles and standing for 15 minutes, and curing at 80°C for 48 hours to obtain a weather-resistant coating for photovoltaic modules; The modified resin is prepared by the following method: Step A1: 1.5 g 3-amino-4-hydroxybenzoic acid, 0.69 g sodium nitrite, 1.19 g copper sulfate pentahydrate and 3 mL concentrated hydrochloric acid were mixed, stirred in an ice-salt bath at 5° C., the pH was adjusted to 7-8, and then 7 g 11-aminoundecyltrimethoxysilane, 7 g ethanol-water mixed solution and 4 g hydroxypropyl methacrylate were added, and the mixture was mixed at 35° C. for 10 min, and then the mixture was heated to 60° C., filtered and washed to obtain intermediate 1. The volume ratio of ethanol to water in the ethanol-water mixed solution was 4:1; Step A2: 6.0 g of m-phenylenediamine and 8 g of intermediate 1 were mixed, the temperature was raised to 25°C, the reaction was carried out for 2 h, 2.2 g of 4'-chloro-2-hydroxy-4-methoxybenzophenone and 20 mL of dioxane were added and mixed under nitrogen protection, the mixture was heated to 65°C, the reaction was carried out for 6 h, the mixture was filtered, washed, and dried at 45°C to obtain intermediate 2; Step A3: 7 g of methyl methacrylate, 7 g of butyl acrylate, 4 g of intermediate 2, 1.5 g of 1H, 1H-perfluoropropyl methacrylate and 0.7 g of methacrylic acid were mixed and stirred for 10 min, and then 0.55 g of azobisisobutyronitrile, 1.5 mL of dodecanethiol and 20 mL of ethanol were added and stirred to mix evenly, the temperature was raised to 80° C., the reaction was carried out for 3 h, and the modified resin was obtained by cooling to room temperature; The composite filler is prepared by the following method: Step B1: 4 g of nano zinc oxide and 100 mL of toluene were mixed, placed in a constant temperature water bath, stirred at 80° C. for 15 min, 2 mL of dodecyltrimethoxysilane was added, reacted at 80° C. for 9 h, and then 0.25 mL of γ-aminopropyltriethoxysilane was added, reacted at 80° C. for 8 h, centrifuged, washed, ultrasonically dispersed and cleaned, centrifuged, dried at 60° C., and ground to obtain superhydrophobic zinc oxide; Step B2: 100 g of superhydrophobic zinc oxide and 200 mL of anhydrous ethanol were mixed, ultrasonically dispersed for 30 min, and 7 g of cinnamic acid was added under nitrogen protection. The mixture was heated to 60° C., reacted for 3 h, centrifuged, washed, and dried at 45° C. to obtain a composite filler.

[0015] Comparative Example 1: This comparative example is a weather-resistant coating for photovoltaic modules. The difference from Example 3 is that an equal amount of acrylic resin is used to replace the modified resin prepared in Example 3, and the rest is the same.

[0016] Comparative Example 2: This comparative example is a weather-resistant coating for photovoltaic modules. The difference from Example 3 is that an equal amount of conductive mica powder is used to replace the composite filler prepared in Example 3, and the rest is the same.

[0017] Performance test: The photovoltaic modules prepared in Examples 1-3 and Comparative Examples 1-2 were made into standard test sizes with weather-resistant coatings, and irradiated for 40 hours at a vertical distance of 10 cm using a UVC-LED disinfection lamp (30 W, 254 nm wavelength). The color difference before and after UVC-LED irradiation was detected according to the CIE1976L*a*b* standard. Friction and wear tests were performed according to YY / T 0113-2015 (the smaller the value of the wear index, the better the wear resistance). Water absorption was tested according to GB / T 1034-2008 standard, and the thickness of the test piece was 2 mm. Antibacterial testing was performed according to GB / T 1727-1992 standard, and chemical corrosion resistance time test was performed. The test results are shown in the following table:

[0018] It can be seen from the test data in the table that the weather-resistant coating for photovoltaic modules prepared in Example 1 not only has good UV resistance and corrosion resistance, but also has excellent water resistance and antibacterial effects, extending the service life of the material. It can also be seen from the above table that the weather-resistant coating for photovoltaic modules prepared by the present invention has excellent wear resistance, thereby improving the comprehensive performance of the weather-resistant coating for photovoltaic modules.

[0019] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a weather-resistant coating for a photovoltaic module, characterized in that: The following steps are involved: S1, placing the modified resin in a solvent and ultrasonically treating it for 10-20 minutes to obtain a dispersion; S2, adding the composite filler, plasticizer, curing agent and additive into the dispersion and stirring for 5-10 minutes to mix evenly to obtain a mixed coating; S3, stirring the mixed coating in a vacuum environment to remove bubbles and standing for 5-15 minutes, and curing at 70-80°C for 36-48 hours to obtain a weather-resistant coating for photovoltaic modules; The modified resin is prepared by the following method: Step A1: 3-amino-4-hydroxybenzoic acid, sodium nitrite, copper sulfate pentahydrate and concentrated hydrochloric acid are mixed, stirred in an ice-salt bath at 0-5°C, the pH is adjusted to 7-8, 11-aminoundecyltrimethoxysilane, ethanol-water mixed solution and hydroxypropyl methacrylate are added, and the mixture is mixed at 35°C for 10 minutes, and then the mixture is heated to 60°C, filtered and washed to obtain intermediate 1; Step A2: m-phenylenediamine and intermediate 1 are mixed, heated to 25°C, reacted for 2h, and under nitrogen protection, 4'-chloro-2-hydroxy-4-methoxybenzophenone and dioxane are added, mixed and stirred, heated to 65°C, reacted for 6h, filtered, washed, and dried at 45°C to obtain intermediate 2; Step A3: Methyl methacrylate, butyl acrylate, intermediate 2, 1H,1H-perfluoropropyl methacrylate and methacrylic acid were mixed and stirred for 10 min, and then azobisisobutyronitrile, dodecanethiol and ethanol were added and stirred to mix evenly, the temperature was raised to 70-80°C, the reaction was carried out for 3 h, and the modified resin was obtained by cooling to room temperature.

2. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 1, characterized in that: In step A1, the dosage ratio of 3-amino-4-hydroxybenzoic acid, sodium nitrite, copper sulfate pentahydrate, concentrated hydrochloric acid, 11-aminoundecyltrimethoxysilane, ethanol-water mixed solution, and hydroxypropyl methacrylate is 1-1.5 g: 0.69 g: 1.04-1.19 g: 3 mL: 5-7 g: 5-7 g: 2-4 g, and the volume ratio of ethanol to water in the ethanol-water mixed solution is 4:

1.

3. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 1, characterized in that: In step A2, the usage ratio of interphenylenediamine, intermediate 1, 4'-chloro-2-hydroxy-4-methoxybenzophenone and dioxane is 6.0 g: 6-8 g: 1.0-2.2 g: 10-20 mL.

4. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 1, characterized in that: In step A3, the usage ratio of methyl methacrylate, butyl acrylate, intermediate 2, 1H,1H-perfluoropropyl methacrylate, methacrylic acid, azobisisobutyronitrile, dodecanethiol and ethanol is 5-7 g: 5-7 g: 2-4 g: 0.5-1.5 g: 0.3-0.7 g: 0.35-0.55 g: 0.5-1.5 mL: 20 mL.

5. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 1, characterized in that: The composite filler is prepared by the following method: Step B1: Mix nano zinc oxide and toluene, place in a constant temperature water bath, stir at 80°C for 15 minutes, add dodecyltrimethoxysilane, react at 80°C for 9 hours, then add γ-aminopropyltriethoxysilane, react at 80°C for 8 hours, centrifuge, wash, ultrasonically disperse and clean, centrifuge, dry at 60°C, and grind to obtain super hydrophobic zinc oxide; Step B2: Super-hydrophobic zinc oxide and anhydrous ethanol are mixed, ultrasonically dispersed for 30 minutes, and cinnamic acid is added under nitrogen protection. The mixture is heated to 60° C., reacted for 3 hours, centrifuged, washed, and dried at 45° C. to obtain a composite filler.

6. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 5, characterized in that: In step B1, the usage ratio of nano zinc oxide, toluene, dodecyltrimethoxysilane and γ-aminopropyltriethoxysilane is 2.5-4 g: 80-100 mL: 1-2 mL: 0.1-0.25 mL.

7. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 5, characterized in that: In step B2, the usage ratio of superhydrophobic zinc oxide, anhydrous ethanol and cinnamic acid is 60-100 g: 120-200 mL: 5-7 g.

8. The method for preparing a weather-resistant coating for a photovoltaic module according to claim 1, characterized in that: The curing agent is hexamethylene diisocyanate, the auxiliary agent is dibutyltin dilaurate, the solvent is butyl acetate, and the plasticizer is polyethylene glycol.

9. A weather-resistant coating for a photovoltaic module, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • An expandable graphite superhydrophobic anticorrosion coating formulation and preparation method

    CN114933837A

  • Waterproof and anticorrosive material for concrete bridge and preparation method of waterproof and anticorrosive material

    CN116376419A

  • Preparation process of environment-friendly water-permeable concrete

    CN118125768A

  • Ultraviolet-proof titanium dioxide-based automobile coating liquid and preparation method thereof

    CN118325413A

  • Low-temperature-resistant modified PC material and production process thereof

    CN118909422A

Cited By

  • Copper-doped titanium dioxide antibacterial skin-care window film

    CN121379345A